A, B, and C are arbitrary wffs, how would I prove that:
{A->B, B->C} |- (A->C)
1) Α===>Β............................................ ......................given
2) B====>C........................................... ........................given
3) A................................................. ...........................assumption
4) B................................................. ..........................1,3 M.Ponens
5) C................................................. ...........................2,4 M.Ponens
6) A=====>C.......................................... ..................BY using the deduction theorem or called differently the law of conditional proof
from the lines 3 to 5